Answer :
Answer:
B(-2, -7)
Step-by-step explanation:
Midpoint is (0, -3)
A(x₁, y₁) B(x₂, y₂)
A(2, 1)
[tex]Midpoint = (\frac{x_{1} + x_{2} }{2}, \frac{y_{1} + y_{2} }{2} )\\\\Midpoint = (\frac{2+ x_{2} }{2}, \frac{1 + y_{2} }{2} )[/tex]
[tex](0, -3) = (\frac{2+ x_{2} }{2}, \frac{1 + y_{2} }{2} )[/tex]
[tex]\frac{2+ x_{2} }{2} = 0\\\\2 + x_{2} = 0\ \ \ \ times\ both\ sides\ by\ 2\\x_{2} = -2\ \ \ \ subtract\ both\ sides\ by\ 2[/tex]
[tex]\frac{1 + y_{2} }{2} = -3\\\\1 + y_{2} = -6\ \ \ \ times\ both\ sides\ by\ 2\\y_{2} = -7\ \ \ \ subtract\ both\ sides\ by\ 1[/tex]
∴ B(-2, -7)